Pharmacist, general practitioner, and nurse perceptions, experiences, and knowledge of medication dosage form modification - Nguyen TMU; Lau ETL; Steadman KJ; Cichero JAY; Dingle K; Nissen LM (Dove Medical Press, 2013)
Thi-My-Uyen Nguyen,1 Esther TL Lau,1,3 Kathryn J Steadman,1 Julie AY Cichero,1 Kaeleen Dingle,2 Lisa M Nissen1,3 1School of Pharmacy, University of Queensland, Brisbane, QLD, Australia; 2School of Public Health, Queensland University of Technology, Brisbane, QLD, Australia; 3School of Clinical Sciences, Queensland University of Technology, Brisbane, QLD, Australia Background: People often modify oral solid dosage forms when they experience difficulty swallowing them. Modifying dosage forms may cause adverse effects to the patient, and the person undertaking the modification. Pharmacists are often the first point of contact for people in the general community seeking advice regarding medications. Nurses are at the forefront of administering medications to patients and are likely to be most directly affected by a patient’s swallowing ability, while general practitioners (GPs) are expected to consider swallowing abilities when prescribing medications. Objective: To compare the perspectives and experiences of GPs, pharmacists, and nurses regarding medication dosage form modification and their knowledge of medication modification. Method: Questionnaires tailored to each profession were posted to 630 GPs, and links to an online version were distributed to 2,090 pharmacists and 505 nurses. Results: When compared to pharmacists and GPs, nurses perceived that a greater proportion of the general community modified solid dosage forms. Pharmacists and GPs were most likely to consider allergies and medical history when deciding whether to prescribe or dispense a medicine, while nurses’ priorities were allergies and swallowing problems when administering medications. While nurses were more likely to ask their patients about their ability to swallow medications, most health professionals reported that patients “rarely” or “never” volunteered information about swallowing difficulties. The majority of health professionals would advise a patient to crush or split noncoated non-sustained-release tablets, and would consult colleagues or reference sources for sustained-release or coated tablets. Health professionals appeared to rely heavily upon the suffix attached to medication names (which suggest modified release properties) to identify potential problems associated with modifying medications. Conclusion: The different professional roles and responsibilities of GPs, pharmacists, and nurses are associated with different perspectives of, and experiences with, people modifying medications in the general community and knowledge about consequences of medication modification. Keywords: crushing tablets, opening capsules, dosage form modification, health professional